2005
DOI: 10.1159/000083038
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Onset of Cigarette, Alcohol and Cannabis Use and Later Drug Use Patterns: An Analysis of a Survey in European Metropolises

Abstract: Objectives: The study presents data about age of onset of alcohol, cigarette and cannabis use and investigates the association between age of onset and later drug use patterns. Methods: Using a sample from a cross-sectional multi-site study, personal interviews were conducted with 3,503 individuals aged 12–49 years. Last-month prevalence, age of onset and associations with subsequent use patterns were investigated. Results: Having started with cannabis before the age of 16 years was associated with an odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 71 publications
4
25
0
Order By: Relevance
“…Initially, in line with previous research, we hypothesised that for a given individual, a common drug use liability would be characterised by early initiation, poly-substance use and higher levels of use [23,24,27,28] . Item-response theory (IRT) modelling, a methodology previously used in the area of addiction [29,30] , was then used to construct 2 latent variables exploring early onset and current use: -The early onset latent variable was built using 7 dummy variables exploring an age at initiation under 25th percentile for tobacco (initiation under 13), first drunkenness (under 15), cannabis (under 15), inhalants (under 15), depressants (at least 1 substance among heroin, buprenorphine, methadone, GHB or ketamine), stimulants (cocaine, crack, ecstasy, amphetamines or MDMA), and hallucinogens (mushrooms or LSD; under 18 for these latter 3 classes); -The current substance use latent variable was built with 7 other dummy variables: tobacco current daily use, current hazardous alcohol use according to the alcohol use disorders identification test [31] , cannabis use reported in the past month, and inhalants, depressants, stimulants and hallucinogens use reported in the past 12 months.…”
Section: Methodsmentioning
confidence: 90%
“…Initially, in line with previous research, we hypothesised that for a given individual, a common drug use liability would be characterised by early initiation, poly-substance use and higher levels of use [23,24,27,28] . Item-response theory (IRT) modelling, a methodology previously used in the area of addiction [29,30] , was then used to construct 2 latent variables exploring early onset and current use: -The early onset latent variable was built using 7 dummy variables exploring an age at initiation under 25th percentile for tobacco (initiation under 13), first drunkenness (under 15), cannabis (under 15), inhalants (under 15), depressants (at least 1 substance among heroin, buprenorphine, methadone, GHB or ketamine), stimulants (cocaine, crack, ecstasy, amphetamines or MDMA), and hallucinogens (mushrooms or LSD; under 18 for these latter 3 classes); -The current substance use latent variable was built with 7 other dummy variables: tobacco current daily use, current hazardous alcohol use according to the alcohol use disorders identification test [31] , cannabis use reported in the past month, and inhalants, depressants, stimulants and hallucinogens use reported in the past 12 months.…”
Section: Methodsmentioning
confidence: 90%
“…Studies have adopted cut-points for early onset of age 12 or younger (De Genna et al, 2009), age 13 or younger (Baumeister and Tossmann, 2005;Bossarte and Swahn, 2008;King and Chassin, 2007), age 14 or younger (Hingson et al, 2000;McGue and Iacono, 2005;Sartor et al, 2009), and age 15 or younger (Humphrey and Friedman, 1986). In the present analyses, early initiation of alcohol use is defi ned as drinking at age 14 or younger, the most common defi nition in this literature.…”
Section: Defi Nition Of Early-onset Drinkingmentioning
confidence: 99%
“…Using data from a large U.S. epidemiological survey, Grant and Dawson (1997) reported that individuals who had used alcohol prior to age 15 were four times more likely to develop alcohol dependence in adulthood than individuals who had first tried alcohol after age 20. This finding, which suggests that risk for alcoholism is for some individuals established very early in life, has had a major impact on the conceptualization of both effective preventions and the origins alcoholism (Baumeister and Tossmann, 2005;Pitkänen et al, 2005;Stewart et al, 2005). Nonetheless, the implications of this research for prevention and developmental models of alcoholism depend on the causal basis for the association of early drinking with later alcoholism.…”
Section: Introductionmentioning
confidence: 97%